A convenient way to represent fatigue crack growth in structural adhesives. Issue 4 (29th September 2014) - Jones, R.; Hu, W.; Kinloch, A. J.
Abstract The present paper examines crack growth in a range of aerospace and automotive structural adhesive joints under cyclic‐fatigue loadings. It is shown that cyclic‐fatigue crack growth in such materials can be represented by a form of the Hartman–Schijve crack‐growth equation, which aims to give a unique and linear 'master' representation for the fatigue data points that have been experimentally obtained, as well as enabling the basic fatigue relationship to be readily computed. This relationship is shown to capture the experimental data representing the effects of test conditions, such as R‐ratio and test temperature. It also captures the typical scatter often seen in the fatigue crack‐growth tests, especially at low values of the fatigue crack‐growth rate. The methodology is also shown to be applicable to both Mode I (opening tensile), Mode II (in‐plane shear) and Mixed‐Mode I/II fatigue loadings. Indeed, it has been demonstrated that the fatigue behaviour of structural adhesives under both Mode I and Mode II loadings may be described by one unique 'master' linear relationship via the Hartman–Schijve approach.